The creation of a mental skills training program in elite youth tennis: A coach-driven approach to developing resilient, confident competitors - Lauer, E. E.; Lerman, M.; Zakrajsek, R. A.; Lauer, L. (International Sport Coaching Journal, 2020)
In this paper, we describe the development and content of a mental skills training (MST) program and how a strength and conditioning coach/certified mental coach delivered this program within a United States Tennis Association (USTA) Player Development (PD) program. The purpose of the MST program was to create resilient, confident youth tennis competitors. Specific mental strategies (i.e., journaling, routines, breathing, imagery, self-talk) were identified to best meet the objectives of the MST program and were delivered using a three-pronged approach: (a) classroom lessons, (b) strength and conditioning sessions and on-court lessons, and (c) homework assignments. Specific ways that the USTA PD coaches reinforced the use of these strategies during tennis practice are described. Recommendations for coaches to integrate an MST program in high-performance youth sport environments are also provided.